Tuning the Selective Ethanol Oxidation on Tensile‐Trained Pt(110) Surface by Ir Single Atoms. Issue 33 (24th July 2022) - Zhang, Genlei; Cao, Dongjie; Guo, Shiyu; Fang, Yan; Wang, Qi; Cheng, Sheng; Zuo, Wansheng; Yang, Zhenzhen; Cui, Peng
Abstract: Development of efficient and robust electrocatalysts for complete oxidation of ethanol is critical for the commercialization of direct ethanol fuel cells. However, the complete oxidation of ethanol suffers from poor efficiency due to the low C1 pathway selectivity. Herein, single‐atomic Ir (Ir1 ) on hcp ‐PtPb/ fcc ‐Pt core–shell hexagonal nanoplates (PtPb@PtIr1 HNPs) enclosed by Pt(110) surface with a 7.2% tensile strain is constructed to drive complete electro‐oxidation of ethanol. Benefiting from the construction of Ir1 sites, the PtPb@PtIr1 HNPs exhibit a Faraday efficiency of 57.93% for the C1 pathway, which is ≈8.3 times higher than that of the commercial Pt/C‐JM. Furthermore, the PtPb@PtIr1 HNPs show a top‐ranked electro‐activity achieving 45.1‐fold and 56.3‐fold higher than the specific and mass activities of Pt/C‐JM, respectively. Meanwhile, the durability can be significantly enhanced by the construction of Ir1 sites. Density functional theory calculations indicate that the strong synergy on the PtPb@PtIr1 HNPs surface significantly promotes the breaking of CC bond of CH2 CO* and facilitates CO oxidation and suppresses the deactivation of the catalyst. This work offers a unique single‐atom approach using low‐coordination active sites on shape‐controlled nanocrystals to tune the selectivity and activity toward complicated catalytic reactions. Abstract : The single‐atomic Ir‐tailored Pt(110) surface with tensile strain is constructed for efficient complete electro‐oxidation of ethanol. It is found that isolated Ir atoms can favor the CC bond cleavage of C2 intermediates and promote the complete oxidation of ethanol to CO2 along the C1 pathway.